The Influence of Altruism, Moral Obligation, and Halal Brand Image on Purchase Intention - Fera Anggraini; Soepatini Soepatini (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the effect of altruism, moral obligation, and halal brand image on purchase intention of Hanasui cosmetics with Electronic Word of Mouth (E-WOM) as an intervening variable. As consumer awareness of halal products increases, factors such as moral values ​​and digital communication become important elements in purchasing decisions. This study uses a quantitative approach with a survey method through a questionnaire distributed to 150 respondents. The data collected were analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS 3 software. The results showed that altruism, moral obligation, and halal brand image have a positive and significant effect on purchase intention of Hanasui cosmetics. In addition, E-WOM was proven to mediate the relationship between altruism, moral obligation, and halal brand image on purchase intention. This confirms that digital communication through reviews and recommendations from other users plays an important role in shaping consumer perceptions and increasing trust in halal products. The implications of this study can help halal cosmetic companies in designing more effective marketing strategies by utilizing digital communication and building a strong brand image among consumers.